BirdMoE: Reducing Communication Costs for Mixture-of-Experts Training Using Load-Aware Bi-random Quantization - Wu, Donglei; Yang, Weihao; Zou, Xiangyu; Jia, Jinda; Tao, Dingwen; Xia, Wen; Tian, Zhihong (2025 62nd ACM/IEEE Design Automation Conference (DAC), 2025)
Mixture-of-Experts (MoE) model parallelism is prevalent in training Large Language Models (e.g., ChatGPT). However, the intensive all-to-all collective communication of the MoE layer's intermediate computing results substantially degrades MoE training efficiency. In this paper, we propose BirdMoE, a novel load-aware communication compression technique with Bi-random quantization for MoE training with two core modules. Specifically, BirdMoE employs a lightweight Random Quantization (RQ) with expectation invariance property to efficiently map the floating-point intermediate computing results into integers while maintaining the MoE training quality. Additionally, BirdMoE utilizes a Mixed Precision (MP) strategy to dynamically balance the communication loads among expert nodes, significantly improving all-to-all communication efficiency for the MoE training system. Experiments on four typical MoE training tasks demonstrate that BirdMoE achieves higher 4.06 ×- 10.44 × total communication compression ratios and 1.18 ×-5.27 × training speedup compared with the state-of-the-art compression techniques while maintaining the MoE training quality.